1999
DOI: 10.4138/2034
|View full text |Cite
|
Sign up to set email alerts
|

NW-oriented features on both sides of the Atlantic Ocean: evidence for a Paleozoic collision that formed the Labrador-Biscay wrench fault zone?

Abstract: Northwest-oriented features have been recognized for many years as fundamental components of the geology of the northwestern European continental shelves. Similarly oriented lineations and faults have been mapped throughout southwestern Britain, western France and across the English Channel. On land in Europe, similar trends are identified as far east as the Urals. Features of similar orientation, extending over a broad area on the North American continental shelf, have recently been identified from geophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…3) along the edges of the Carboniferous basins (Gibling et al 1987) formed initially as strike-slip faults, later re-activated as normal faults. Lefort and Miller (1999) suggested that the strong northwest-oriented, megalineaments present over the island could be related to wrench faulting formed during the collision between Gondwana and Laurasia in the late Paleozoic, during the closure of the remaining oceanic tract between the two continents.…”
Section: (3)mentioning
confidence: 99%
See 3 more Smart Citations
“…3) along the edges of the Carboniferous basins (Gibling et al 1987) formed initially as strike-slip faults, later re-activated as normal faults. Lefort and Miller (1999) suggested that the strong northwest-oriented, megalineaments present over the island could be related to wrench faulting formed during the collision between Gondwana and Laurasia in the late Paleozoic, during the closure of the remaining oceanic tract between the two continents.…”
Section: (3)mentioning
confidence: 99%
“…This rifting resulted in reactivation of the CobequidChedabucto and Hollow Fault-Aspy Fault systems, as well as reactivation of basin-bounding strike-slip faults as normal faults (Faure et al 2006;Herman 2009). Lefort and Miller (1999) suggested that the northwest-to westoriented wrench faults created pre-existing basement weaknesses, which were reactivated during Mesozoic rifting.…”
Section: (3)mentioning
confidence: 99%
See 2 more Smart Citations